Complex water networks visualized by cryogenic electron microscopy of RNA - Rachael C. Kretsch; Shanshan Li; Grigore Pintilie; Michael Z. Palo; David A. Case; Rhiju Das; Kaiming Zhang; Wah Chiu (Nature, 2025)
Abstract The stability and function of biomolecules are directly influenced by their myriad interactions with water1–16. Here we investigated water through cryogenic electron microscopy (cryo-EM) on a highly solvated molecule: the Tetrahymena ribozyme. By using segmentation-guided water and ion modelling (SWIM)17,18, an approach combining resolvability and chemical parameters, we automatically modelled and cross-validated water molecules and Mg2+ ions in the ribozyme core, revealing the extensive involvement of water in mediating RNA non-canonical interactions. Unexpectedly, in regions where SWIM does not model ordered water, we observed highly similar densities in both cryo-EM maps. In many of these regions, the cryo-EM densities superimpose with complex water networks predicted by molecular dynamics, supporting their assignment as water and suggesting a biophysical explanation for their elusiveness to conventional atomic coordinate modelling. Our study demonstrates an approach to unveil both rigid and flexible waters that surround biomolecules through cryo-EM map densities, statistical and chemical metrics, and molecular dynamics simulations.